A novel chimeric PD1-NKG2D-41BB receptor enhances antitumor activity of NK92 cells against human lung cancer H1299 cells by triggering pyroptosis. (June 2020) - Lu, Chengui; Guo, Changjiang; Chen, Han; Zhang, Huiyong; Zhi, Lingtong; Lv, Tanyu; Li, Mingfeng; Niu, Zhiyuan; Lu, Ping; Zhu, Wuling
Highlights: NK-tailored CCCR enhances cytotoxicity of NK92 cells against H1299 lung cancer cells in vitro . CCCR-NK92 cells eliminate H1299 cells via pyroptosis mediated by GSDME. CCCR-NK92 cells exerts potent antitumor activity against H1299 lung tumor in vivo . Abstract: Chimeric antigen receptor (CAR)-modified adoptive natural killer (NK) cells represent a promising immunotherapeutic modality for cancer treatment but face many challenges in solid tumors. One major obstacle is the immune-suppressive effects induced by inhibitory receptors (IR) including PD1. To interfere with PD1 signaling to augment CAR-NK cells' activity against solid tumors, we rationally designed a novel chimeric costimulatory converting receptor (CCCR), comprising mainly the extracellular domain of PD1, transmembrane and cytoplasmic domains of NKG2D, and the cytoplasmic domain of 41BB. This NK-tailored CCCR was able to switch the negative PD1 signal to an activating signal and hence reversed the immune suppressive effects of PD1. The CCCR-modified NK92 (CCCR-NK92) cells retained typical characteristics of NK cells and exhibited enhanced antitumor activity against human lung cancer H1299 cells in vitro compared with untransduced NK92 cells. The rapid clearance of H1299 cells was caused by CCCR-NK92 cell-induced extensive pyroptosis. In a lung cancer xenograft model, CCCR-NK92 cells signiﬁcantly inhibited tumor growth. Our results highlight a promising immunotherapeutic potential of using NK-tailored CCCR engineered NK92 cells to treat human lung cancer.